2019
DOI: 10.1016/j.yclnex.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

The seluang fish (Rasbora spp.) diet to improve neurotoxicity of endosulfan-induced intrauterine pup's brain through of oxidative mechanism

Abstract: levels were not significantly different (p ¼ 0.483). Group P1 and P2 were not different significantly in the serum and brain serotonin, and brain SOD levels. The brain H 2 O 2 (p < 0.001) and MDA levels (p < 0.001) were different significantly. We concluded that seluang fish diet was able to repair oxidative stress in the brains of rats due to endosulfan induction during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…17 Seluang was recommended as calcium supplementation since it contains abundant organic calcium. 18 Result from other studies 19,20 showed that 100 grams of Seluang contain 80 mg calcium, 224 mg phosphorus, and 4.7 mg iron. Organic calcium comes with other trace elements that could enhance or benefit participants.…”
Section: Discussionmentioning
confidence: 99%
“…17 Seluang was recommended as calcium supplementation since it contains abundant organic calcium. 18 Result from other studies 19,20 showed that 100 grams of Seluang contain 80 mg calcium, 224 mg phosphorus, and 4.7 mg iron. Organic calcium comes with other trace elements that could enhance or benefit participants.…”
Section: Discussionmentioning
confidence: 99%